2018
DOI: 10.20448/journal.518.2018.31.15.25
|View full text |Cite
|
Sign up to set email alerts
|

Business Process Reengineering Resources and the Performance of Quoted Brewing Firms in Nigeria

Abstract: The study examined the effect of Business Process Reengineering (BPR) resources on the performance of brewing firms in Nigeria. Following the Kassahun (2012) BPR perspectives, the study grouped BPR resources into financial, human and technological resources. A sample of 746 employees was randomly selected from a population of 3500 from five brewing firms quoted in the Nigerian stock exchange. The Likert-type instrument of five-point scale used for data collection has a Cronbach alpha coefficient of 0.85. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In conclusion, organizations that adopt business process re-engineering have a different level of success, and the success of an individual organization depends on the balance between the organizational structure of the organization and the environment. In another study by Akam et al, (2018)that examined the effect of BPR resources on performance of brewing firms in Nigeria where the results of this study showed that financial and technological resources were in proper use while human resources were moderate. Also, the performance of companies currently has a top five-point rating as BPR resources have a significant impact of 94% on corporate performance.…”
Section: The Important Of Bpr For Organizational Performancementioning
confidence: 95%
“…In conclusion, organizations that adopt business process re-engineering have a different level of success, and the success of an individual organization depends on the balance between the organizational structure of the organization and the environment. In another study by Akam et al, (2018)that examined the effect of BPR resources on performance of brewing firms in Nigeria where the results of this study showed that financial and technological resources were in proper use while human resources were moderate. Also, the performance of companies currently has a top five-point rating as BPR resources have a significant impact of 94% on corporate performance.…”
Section: The Important Of Bpr For Organizational Performancementioning
confidence: 95%
“…Several studies have confirmed the efficacy of business process reengineering in influencing organizational performance in various sectors like educational sector (Herminawaty, 2016), banking sub-sector (Husameddin & Mohammad, 2018); Akam et al, 2018); Orogbu, Onyeizugbe & Onuzulike, 2015); tourist (Naveeda, 2014); and even public sector (Mwaura, 2016).Thus, this study deems it fit to see if the similar results between business process reengineering and organizational performance are found in food and beverage industry in Nigeria. It was further observed that all the studies reviewed failed to include organizational resources (human, physical and financial resources), innovative thinking and process function as proxies for business process reengineering, hence, the need for this study.…”
Section: Introductionmentioning
confidence: 95%
“…In other words, it emphasizes managing the business process and not necessarily the product per se (Grover, Jeong, Keitinger & Jeng, 2011). Akam, Okeke, Kekeocha and Onuorah (2018) stated that BPR enables organizations to improve productivity and relationships with customers, and reduce time to launch new products and services in terms of cost, quality, customer satisfaction and shareholders' value by identifying and reengineering the important processes of the firm. Zigiaris (2000) posited that BPR is a new practice that replaces ineffective organizational processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations